2021
DOI: 10.1002/cnm.3518
|View full text |Cite
|
Sign up to set email alerts
|

The impact of shape uncertainty on aortic‐valve pressure‐drop computations

Abstract: Patient‐specific image‐based computational fluid dynamics (CFD) is widely adopted in the cardiovascular research community to study hemodynamics, and will become increasingly important for personalized medicine. However, segmentation of the flow domain is not exact and geometric uncertainty can be expected which propagates through the computational model, leading to uncertainty in model output. Seventy‐four aortic‐valves were segmented from computed tomography images at peak systole. Statistical shape modeling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 70 publications
(162 reference statements)
1
4
0
Order By: Relevance
“…Furthermore, the template used to generate the synthetic geometries is very suitable for finite element, CFD or FSI simulations, since it does not contain any holes or distorted elements. Moreover, its refinement level aligns with, or even surpasses the refinement reported by Hoeijmakers et al 7 As a result, the synthetic geometries are well‐suited for simulations and require minimal pre‐processing steps before integration into a simulation pipeline.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Furthermore, the template used to generate the synthetic geometries is very suitable for finite element, CFD or FSI simulations, since it does not contain any holes or distorted elements. Moreover, its refinement level aligns with, or even surpasses the refinement reported by Hoeijmakers et al 7 As a result, the synthetic geometries are well‐suited for simulations and require minimal pre‐processing steps before integration into a simulation pipeline.…”
Section: Discussionsupporting
confidence: 58%
“…In silico trials could possibly speed up the clinical introduction of improved TAVI devices. Computational fluid dynamics (CFD) and fluid–structure interaction (FSI) models are typically used to simulate aortic valve dynamics before, 7,8 and after treatment 9–13 . Furthermore, finite element methods can be used to simulate contact forces between the aortic root and the TAVI valve during deployment 14–16 .…”
Section: Introductionmentioning
confidence: 99%
“…In time-critical emergency situations such as a patient undergoing an exacerbation, using CPFD-based modelling as a biomarker to help treatment planning is infeasible due to the turnaround time [16], and a less time-consuming model should be developed. To deliver real-time prediction of clinical quantities of interest, geometric parameters (such as SSM weights) and flow variables can be used to fit machine learning models to simulation data to provide predictions of deposition within minutes [120][121][122]. Morales et al [123] showed that wall-shear stress could be predicted from patient-specific vascular meshes with minimal pre-processing using geometric deep learning, which has been developed for analysing non-Euclidean geometries such as graphs or meshes [124].…”
Section: Plos Onementioning
confidence: 99%
“… 2020 ; Hoeijmakers et al. 2019 , 2020 , 2021 ). However, this requires advanced meshing procedures since valve geometries must be defined a priori within the boundary of the mesh.…”
Section: Introductionmentioning
confidence: 99%